1994
DOI: 10.1111/j.1365-2389.1994.tb00527.x
|View full text |Cite
|
Sign up to set email alerts
|

Ionic‐strength and pH effects on the sorption of cadmium and the surface charge of soils

Abstract: Two Oxisols (Mena and Malanda), a Xeralf and a Xerert from Australia and an Andept (Patua) and a Fragiaqualf (Tokomaru) from New Zealand were used to examine the effect of pH and ionic strength on the surface charge of soil and sorption of cadmium. Adsorption of Cd was measured using water, 0.01 mol dmp3 Ca(NO&, and various concentrations of NaN03 (0.01-1.5 mol dm-3) as background solutions at a range of pH values (3)(4)(5)(6)(7)(8).In all soils, the net surface charge decreased with an increase in pH. The pH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
168
0
33

Year Published

2000
2000
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 487 publications
(230 citation statements)
references
References 40 publications
11
168
0
33
Order By: Relevance
“…The ionic strength-dependent Cd 2þ sorption might be attributed to the weakly complexation of Cd like outer-sphere surface species on the red mud (Sparks, 1995;Goldberg and Johnston, 2001). The elevation of ionic strength could increase the net surface positive charges of the red mud at pH (6.5) below its PZC (8.5), which could drive the competition of Cd 2þ for the sorption sites and change the z potential in the sorption plane, thus decreasing the Cd 2þ sorption on the red mud (Naidu et al, 1994). Therefore, it can be presumed that Cd 2þ was sorbed probably through ion exchange reaction with the positive charges from exchangeable sites and formed outersphere complexes (Angove et al, 1997;Srivastava et al, 2005;Serrano et al, 2009).…”
Section: Sorption Isothermsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ionic strength-dependent Cd 2þ sorption might be attributed to the weakly complexation of Cd like outer-sphere surface species on the red mud (Sparks, 1995;Goldberg and Johnston, 2001). The elevation of ionic strength could increase the net surface positive charges of the red mud at pH (6.5) below its PZC (8.5), which could drive the competition of Cd 2þ for the sorption sites and change the z potential in the sorption plane, thus decreasing the Cd 2þ sorption on the red mud (Naidu et al, 1994). Therefore, it can be presumed that Cd 2þ was sorbed probably through ion exchange reaction with the positive charges from exchangeable sites and formed outersphere complexes (Angove et al, 1997;Srivastava et al, 2005;Serrano et al, 2009).…”
Section: Sorption Isothermsmentioning
confidence: 99%
“…Therefore, it can be presumed that Cd 2þ was sorbed probably through ion exchange reaction with the positive charges from exchangeable sites and formed outersphere complexes (Angove et al, 1997;Srivastava et al, 2005;Serrano et al, 2009). However, Naidu et al (1994) observed that Cd 2þ sorption was increased with the increase of ionic strength at pH below the PZC and attributed the phenomena to the fact that the specific sorption rather than simple ion exchange occurred in the sorption plane. Therefore, the unambiguous information about sorption mechanisms of Cd on red mud still needs to be supplied by other additional evidence.…”
Section: Sorption Isothermsmentioning
confidence: 99%
“…It was reported that the adsorption of Cd in the soil increased rapidly with increasing solution pH within the range of 2-5 (Naidu et al, 1994).…”
Section: The Effect Of Ageing On Bioaccessibility In Soilsmentioning
confidence: 99%
“…The NPK+ CaSi9000 treatment showed the greatest decrease in the rice Cd concentration (up to ∼73 %). These results were partially because of Cd immobilization caused by silicateinduced pH change in the soils, the increase of pH (Table 3), which altered the Cd distribution in soil fractions, reduced the phytoavailable Cd, and increased the allocation of metals into more stable fractions (Naidu et al 1994;Liang et al 2005;. This resulted in the observed significant decrease of Cd concentration in straw and grain.…”
Section: Effect Of Si On CD Concentration In Rice Grainmentioning
confidence: 98%
“…The soil pH substantially affects the bioavailability of As and Cd and their absorption by plants (Reddy and Patrick 1977;Masscheleyn et al 1991;Marin et al 1993;Naidu et al 1994;Chan et al 2008). The soil was slightly acidic with pH 6.0 (Table 3).…”
Section: The Changes Of Ph In Soil After Si Fertilizationmentioning
confidence: 99%